Influence of Competence and Administrative Services on Parents' Satisfaction at SMAIT Thariq Bin Ziyad Bekasi - Yasin, Muhamad; Zaharuddin, Zaharuddin; Adiputra, I Gede (Majapahit Journal of Islamic Finance and Management, 2025)
Schools serve as providers of services to learners and the surrounding community, where the effectiveness and quality of these services shape user satisfaction. This study investigates the influence of educator expertise and administrative efficiency on parental satisfaction at SMAIT Thariq Bin Ziyad Bekasi. A quantitative research approach with descriptive and analytical designs was employed, involving 85 respondents selected using the Slovin formula. Data evaluation was performed through t-tests, F-tests, and determination coefficients via SPSS version 25.0. Results show that educator competence partially contributes positively and significantly to parental satisfaction, with an R² of 0.151 (15.1%), while administrative efficiency similarly exerts a significant positive partial effect with an R² of 0.135 (13.5%). When considered together, both competence and administrative efficiency have a meaningful positive impact on parental satisfaction (R² = 0.416 or 41.6%), leaving 58.4% of variation explained by other external factors. These findings highlight the necessity of enhancing both staff capabilities and administrative processes to maximize parental satisfaction.